Factors affecting preparation and evaluation of Kitorolac tromethamine microsponges for ocular use - Wid F. Neamah; Nidhal K. Maraie (College of Pharmacy / Mustansiriyah University, 2020)
Ketorolac Tromethamine (KT) is prepared for the first time by double emulsion procedure. The current research involves preparation and evaluation of microsponges for ocular applications. This work included preparation of sixteen formulas of KT-microsponges by double emulsion (w/o/w) method using poly lactic-co-glycolic acid (PLGA) as a polymer and poly vinyl alcohol (PVA) as a stabilizer, with different mixer types for different time and power. The prepared microsponges were characterized by Scanning Electron Microscopy (SEM) to investigate the morphology and particle size, the entrapment efficacy and percentage yield were calculated as well as in vitro drug release. Best formula (F14) of KT-microsponges had EE (74%), % yield (83%) with initial drug release (approximately 21% within the first fifteen days) which continued to reach (approximately 86% within 90 days) by using 30% of  PLGA  concentration with 0.05% of PVA and 200 ml of the external aqueous phase using a probe sonicator for 4 minutes at 200 Watt power. This formulation technique will be the interest of pharmaceutical company.